E-067 Intra-arterial nicardipine via guide catheter for the treatment of symptomatic vasospasm following aneurysmal subarachnoid hemorrhage. (16th November 2010) - Pandey, P; Dodd, R; Do, H; Steinberg, G; Marks, M
Abstract : Introduction: Delayed ischemic neurological deficits secondary to cerebral vasospasm is a major cause of morbidity and mortality following aneurysmal subarachnoid hemorrhage (SAH). Nicardipine has previously been used to treat vasospasm utilizing superselective microcatheter injections. We here describe a new and simple method of treatment of vasospasm, with slow infusion of nicardipine from a cervical guide catheter. Materials and methods: 27 patients with symptomatic vasospasm following SAH were treated over the past 3 years with cervical catheter infusions (12 patients who underwent angioplasty and/or microcatheter infusion of nicardipine as firstline treatment of vasospasm were not included). Nicardipine was infused at a starting rate of 20 mg/h for 30–60 min. The dose was calibrated to maintain mean arterial pressure above 90 mm Hg. Angioplasty was used in severe cases at the operator's discretion. The outcome at discharge and follow-up was evaluated using Glasgow Outcome Scale (GOS). Results: 27 patients (17 women, 12 men, 26–66 years, mean 49.8) received intra-arterial therapy for vasospasm. The Hunt and Hess grade was II (n=6), III (n=15) and IV (n=6). Fisher grade was III in 26 patients and IV in one patient. Surgery was done in 16 patients (clipping 15, parent vessel occlusion one) while endovascular treatment was done in 11 patients (coiling 10, parent vessel occlusion one). The vasospasm treatment was done at a mean post-hemorrhage date of 7.2 days (4–15, median 7 days). 19 patients had worsening of their mental status along with high transcranial Doppler velocities, while six patients had motor weakness/aphasia. 27 patients underwent 48 sessions of treatment (average 1.8/patient). 15 patients underwent single treatment while 12 had multiple treatments (2–5 treatments). In 48 sessions of treatment, 72 arterial territory infusions of nicardipine were done. The mean dose used in each session of treatment in a patient was 19.2 mg (5–50 mg) while the mean dose in each vessel treated was 12.8 mg (5–30 mg). Additionally, four patients underwent angioplasty for severe vasospasm. In all of these patients, a drip of nicardipine at 20 mg/h was continued through the guide catheter while doing balloon dilatation. In three of these patients, guide catheter infusion had been performed at a previous date, and there was recurrent severe vasospasm. In one patient, there was inadequate angiographic response to guide catheter infusion. 27 had good angiographic and clinical response to the treatment. Two patients had immediate post-clipping infarcts, and one patient died of severe post- hemorrhage cerebral edema. Two patients had new infarcts despite treatment of vasospasm, one patient had progression of pre-existing infarct and one had an infarct due to delayed occlusion of a branch vessel 12 days post-coiling. Overall, 17 patients (62.9%) patients had good outcome (GOS 4, 5) at discharge while 11 patients had poor outcome and one patient died. Follow-up was available in 19 patients, and 18 of them were doing well (GOS 4, 5). Conclusions: Intra-arterial nicardipine is an effective and safe treatment for cerebral vasospasm following SAH. In most patients, the infusion can be performed from the guide catheter, with microcatheter infusion and angioplasty reserved for the more severe and resistant cases.